Sequential Casting Using Multiple Materials: A Bronze Age "Royal Sceptre" From the Halil Rud Valley (Kerman, Iran). Issue 2 (2nd July 2020) - Eskandari, Nasir; Desset, Francois; Maritan, Lara; Cherubini, Arnaldo; Vidale, Massimo
ABSTRACT: This paper deals with a unique artefact currently on exhibit at the archaeological Museum of Jiroft (Kerman, Iran), a large-sized copper or bronze staff inlaid with shell mosaics of contrasting colours. Unfortunately, as it was confiscated with many other objects by the Iranian security forces from illegal excavators, nothing is known of the whereabouts or context of its discovery. It might be one of the largest copper artefacts ever found in Bronze Age sites of the eastern Iranian Plateau. Because of its form, such a unusually elaborated, costly and visually imposing staff must have performed a highly formal symbolic function, hence the hypothetical label of "royal sceptre" (in quotes) proposed in the title. The authors attempt a reconstruction of the original form and manufacturing sequence of this large artefact, discussing its role in the poorly known landscape of the protohistoric metallurgy of south-eastern Iran.